Like father, like son? Power and influence across two Gnassingbé presidencies in Togo. Issue 8 (17th November 2018) - Osei, Anja
ABSTRACT: In personalized authoritarian systems, the death of a leader poses a serious challenge to regime survival. Togo, however, belongs to a small number of countries in which regime collapse has been avoided by the transfer of power to the deceased ruler's son. But can the son simply pick up where the father left off? Combining a theoretically guided single case study with statistical network analysis, this article argues that hereditary succession involves both changes and continuities. While Gnassingbé Eyadema's rule rested on repression, patronage, and a bizarre leadership cult, his son Faure Gnassingbé has partly adapted and reformulated these strategies. The quantitative part of the article is based on a novel data set that contains information on the biographical characteristics and interaction patterns of the deputies in the Togolese parliament. Using exponential random graph models (ERGMs), the article shows that people who have held important positions in the past or belong to the president's ethnic group still play a significant role in the regime elite. The article not only presents detailed insights on a so far under-researched country, but also contributes to the wider literature by showing how mixed-method designs can further our understanding of authoritarian regimes.